(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The purpose of this research is to establish the importance of using an information system for the State Operator Instance (IOE) of the Mexico Connected Project (PMC) in the State of Tabasco, with the aim of improving the registration, control and access to the information of the sites and public spaces in relation to the various activities that are carried out manually for identification, as well as the storage of the information is kept in various archives, which contain varied structures, which generates waste of time and lack of organization at the time of making appropriate decisions for the project. For the development of the solution proposal, it was decided to make an RIA application and use the SCRUM development methodology, using new programming techniques for web environments. As a result, substantial improvements were obtained from the system that allows managing the information of the 6,763 sites proposed to be benefited with high-speed internet in the State, complying with each of the requirements associated with it; Scalable and easy to use for the user. In addition to a unified and homogeneous database.